Long-term follow-up of the MAINTAIN Nephritis Trial, comparing azathioprine and mycophenolate mofetil as maintenance therapy of lupus nephritis. Issue 3 (10th March 2015) - Tamirou, Farah; D'Cruz, David; Sangle, Shirish; Remy, Philippe; Vasconcelos, Carlos; Fiehn, Christoph; Ayala Guttierez, Maria del Mar; Gilboe, Inge-Magrethe; Tektonidou, Maria; Blockmans, Daniel; Ravelingien, Isabelle; le Guern, Véronique; et al.
Abstract : Objective: To report the 10-year follow-up of the MAINTAIN Nephritis Trial comparing azathioprine (AZA) and mycophenolate mofetil (MMF) as maintenance therapy of proliferative lupus nephritis, and to test different definitions of early response as predictors of long-term renal outcome. Methods: In 2014, data on survival, kidney function, 24 h proteinuria, renal flares and other outcomes were collected for the 105 patients randomised between 2002 and 2006, except in 13 lost to follow-up. Results: Death (2 and 3 in the AZA and MMF groups, respectively) and end-stage renal disease (1 and 3, respectively) were rare events. Time to renal flare (22 and 19 flares in AZA and MMF groups, respectively) did not differ between AZA and MMF patients. Patients with good long-term renal outcome had a much more stringent early decrease of 24 h proteinuria compared with patients with poor outcome. The positive predictive value of a 24 h proteinuria <0.5 g/day at 3 months, 6 months and 12 months for a good long-term renal outcome was excellent (between 89% and 92%). Inclusion of renal function and urinalysis in the early response criteria did not impact the value of early proteinuria decrease as long-term prognostic marker. Conclusions: The long-term follow-up data of the MAINTAIN Nephritis Trial do not indicate that MMF is superior to AZA as maintenance therapy in a Caucasian population suffering from proliferative lupus nephritis. Moreover, we confirm the excellent positive predictive value of an early proteinuria decrease for long-term renal outcome. Trial registration number: NCT00204022.